Magnetic carrier, two-component developer, and replenishment developer
By integrating polyrotaxane into the magnetic carrier core of two-component developers, the issues of charge leakage and damage under high stress are mitigated, resulting in improved carrier strength and reduced image defects.
Patent Information
- Application Number
- JP2021038669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-10
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2041-03-10
AI Technical Summary
Magnetic carriers used in two-component developers for electrophotographic image forming are prone to charge leakage and damage under high stress, leading to image fog and toner scattering.
Incorporating polyrotaxane into the magnetic dispersed resin carrier core, which consists of a magnetic material and a dispersed resin, to enhance carrier strength and prevent charge leakage.
The use of polyrotaxane in the magnetic carrier core improves carrier strength, reduces the likelihood of image fog and toner scattering, even under high stress conditions.
Smart Images

Figure 0007669161000001 
Figure 0007669161000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a magnetic carrier, a two-component developer, and a replenishment developer. [Background technology]
[0002] In the developer of an electrophotographic image forming apparatus, a two-component developer is widely used, which is obtained by mixing a magnetic carrier and a toner, frictionally charging the toner, imparting an appropriate amount of positive or negative charge to the toner, and using the charge as a driving force for development. From the viewpoint of obtaining high-quality images, the magnetic carrier used in the two-component developer is required to be unlikely to leak excessive carrier charge in order to sufficiently charge the toner.
[0003] As a magnetic carrier that is less likely to cause leakage of carrier charge, a magnetic material-dispersed resin carrier with a relatively large carrier specific resistance value is known. For example, Patent Document 1 discloses that by using a magnetic material-dispersed resin carrier with controlled magnetization strength and specific resistance value, carrier charge leakage is less likely to occur and good images can be formed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-295523 A [Patent Document 2] WO01 / 083566 [Patent Document 3] JP 2017-31258 A Summary of the Invention [Problem to be solved by the invention]
[0005] One aspect of the present disclosure is to provide a magnetic carrier that can have excellent carrier strength and is less likely to cause image fog and toner scattering even under high stress.
[0006] Another aspect of the present disclosure is directed to providing a two-component developer having the magnetic carrier according to the present disclosure.
[0007] Another aspect of the present disclosure is directed to providing a refill developer having a magnetic carrier according to the present disclosure. [Means for solving the problem]
[0008] According to one aspect of the present disclosure, there is provided a magnetic carrier comprising a magnetic material-dispersed resin carrier core including a magnetic material and a dispersion resin, and a coating resin that coats the surface of the magnetic material-dispersed resin carrier core, The magnetic carrier contains polyrotaxane, The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; The magnetic carrier is characterized by the above.
[0009] According to another aspect of the present disclosure, there is provided a two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to the present disclosure. The present invention provides a two-component developer comprising:
[0010] According to another aspect of the present disclosure, there is provided a replenishment developer containing a toner and a magnetic carrier, comprising: The magnetic carrier is the magnetic carrier according to the present disclosure. The present invention provides a replenishment developer comprising: Effect of the Invention
[0011] According to one embodiment of the present disclosure, it is possible to provide a magnetic carrier that can have excellent carrier strength and is less likely to cause image fog and toner scattering even under high stress.
[0012] According to another aspect of the present disclosure, a two-component developer having the magnetic carrier according to the present disclosure can be provided.
[0013] According to another aspect of the present disclosure, a refill developer having the magnetic carrier according to the present disclosure can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In the present disclosure, the description of "xx or more and xx or less" or "xx to xx" indicating a numerical range means a numerical range including the lower and upper limits, unless otherwise specified. In addition, the magnetic material-dispersed resin carrier core is also simply referred to as a carrier core.
[0015] <Background to the invention> A magnetic material-dispersed resin carrier is a carrier in which magnetic particles are bound with a binder resin, and is therefore known to have a higher specific resistance and less leakage of electric charge than iron powder carriers, ferrite carriers, etc.
[0016] However, the present inventors have found that when a magnetic material-dispersed resin carrier is used to output images at high speed, the carrier may be easily damaged. The present inventors speculate that this is because when an impact is applied to the magnetic material-dispersed resin carrier, stress is likely to concentrate at the interface between the magnetic particles and the binder resin.
[0017] The present inventors also discovered that, as the carrier breaks, the magnetic particles become exposed, the carrier charge becomes more likely to leak, and the toner becomes less likely to be charged, which leads to image fogging and toner scattering in the developing machine. From the viewpoint of obtaining high-quality images even when images are output at high speed, it is naturally required that image fogging and toner scattering are less likely to occur. Therefore, the present inventors recognized that it is necessary to develop a technology for improving the strength of the magnetic material dispersion type resin carrier and for preventing carrier breakage and the associated image fogging and toner scattering from occurring.
[0018] Based on the above considerations, the inventors have investigated various additives in order to obtain a magnetic material-dispersed resin carrier having excellent carrier strength and suppressing image fogging and toner scattering. As a result of intensive investigations, it has been found that incorporating polyrotaxane into a magnetic material-dispersed resin carrier is effective in realizing a carrier having the above-mentioned properties.
[0019] The present inventors speculate that since the cyclic molecules of polyrotaxane can move on chain molecules, when an impact is applied to a magnetic material-dispersed resin carrier containing polyrotaxane, the cyclic molecules can move in response to the impact. As a result, the present inventors speculate that the stress applied to the carrier is easily dispersed and the carrier is less likely to be damaged, so that the carrier can have excellent strength and the associated image fogging and toner scattering are less likely to occur.
[0020] <Polyrotaxane> The polyrotaxane according to the present disclosure has (i) a plurality of cyclic molecules, (ii) a chain molecule that is skewered and included in the rings of the cyclic molecules, and (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecules from being detached from the chain molecule. In general, a molecular assembly in which a chain molecule penetrates the inside of the ring of a cyclic molecule and a bulky molecule is bonded to the end of the axis to bind the cyclic molecules on the chain molecule is called a rotaxane. A molecular assembly in which many cyclic molecules are linked on one chain molecule is called a polyrotaxane. The cyclic molecules are not bonded to the chain molecule and can rotate and move on the chain molecule.
[0021] The content of polyrotaxane is preferably 0.2% by mass or more and 30.0% by mass or less with respect to the mass of the dispersion resin. By being in the above range, it is considered that the stress applied to the carrier is easily dispersed sufficiently, the carrier strength is easily increased, and image fogging and toner scattering are less likely to occur. A more preferable range is 0.5% by mass or more and 25.0% by mass or less.
[0022] The polyrotaxane of the present disclosure can be produced by a publicly known method, for example, the method described in Patent Document 2 or Patent Document 3, or can be obtained and used as a commercially available product (product name: CELME Super Polymer, manufactured by ASM).
[0023] Although the location where the polyrotaxane is contained is not particularly limited, it is preferably contained in the carrier core because it is believed that the stress applied to the vicinity of the magnetic material can be easily dispersed. More preferably, it is contained in a dispersed state in a dispersion resin.
[0024] In the polyrotaxane of the present disclosure, the number of cyclic molecules threaded by one linear molecule (the inclusion amount) is not particularly limited. The inclusion amount can be controlled by the molar ratio of the linear molecule and the cyclic molecule used in producing the polyrotaxane.
[0025] <Cyclic molecules> The cyclic molecules contained in the polyrotaxane are not particularly limited as long as they are capable of including chain molecules and have a ring structure through which the chain molecules can penetrate in a skewered manner.
[0026] Examples of the cyclic molecule of the present disclosure include cyclodextrins, crown ethers, benzocrowns, dibenzocrowns, dicyclohexanocrowns, and derivatives or modified forms thereof. Among these, cyclodextrins are preferred because they are easy to include chain molecules. That is, the cyclic molecule is preferably a molecule having a cyclodextrin skeleton. More preferably, the cyclic molecule is a molecule having at least one cyclodextrin skeleton selected from the group consisting of an α-cyclodextrin skeleton, a β-cyclodextrin skeleton, and a γ-cyclodextrin skeleton. The cyclic molecule may be one type, or two or more types may be used in combination.
[0027] In the present disclosure, a molecule having a cyclodextrin skeleton is regarded as a molecule having a structure synthesized when a cyclodextrin compound or a hydroxyl group of a cyclodextrin compound is subjected to a derivatization reaction.
[0028] <Side chains attached to cyclodextrin> It is preferable that the cyclic molecule of the polyrotaxane is a molecule having a cyclodextrin skeleton, and the molecule having the cyclodextrin skeleton has cyclodextrin and a side chain bonded to the cyclodextrin. Here, the side chain bonded to the cyclodextrin in the present disclosure is treated as a partial structure introduced when a derivatization reaction is performed on a hydroxy group of the cyclodextrin. The side chain may be a linear structure or a branched structure.
[0029] It is believed that the above-mentioned side chains tend to increase the affinity between the polyrotaxane and the resin component. As a result, it is believed that the presence state of the polyrotaxane is less likely to be biased and that it is likely to be contained in a uniformly dispersed state, which is preferable. In addition, it is preferable that the side chains have a polymer structure, and more preferably a polyester structure or a vinyl polymer structure. Examples of the polyester structure include a polymer structure in which a diol and a dicarboxylic acid are condensed, and a polycaprolactone structure. In addition, the vinyl polymer structure is a polymer structure in which a vinyl monomer is polymerized, and examples thereof include a styrene-methyl methacrylate polymer structure.
[0030] The weight average molecular weight of the molecule having the above-mentioned side chain and cyclodextrin skeleton is preferably 1000 to 50000. It has been found that the carrier strength is easily increased and image fogging and toner scattering are less likely to occur within this range. The present inventors believe that this is because not only the impact is dispersed by the movement of the cyclic molecules in the polyrotaxane, but also the polyrotaxane and the resin are entangled, and the scratch resistance of the resin is easily improved due to the self-repairing function of the polyrotaxane. The weight average molecular weight is preferably 2500 or more, more preferably 30000 or less, more preferably 20000 or less, and even more preferably 10000 or less.
[0031] A molecule having a cyclodextrin skeleton that satisfies the above weight-average molecular weight can be produced by bonding a polymer structure to cyclodextrin. For example, it can be produced by introducing a polyester structure into the hydroxyl group of cyclodextrin. It can also be produced by a vinyl polymerization reaction between a cyclodextrin derivative having a vinyl-polymerizable double bond and a vinyl monomer.
[0032] The molecular weight of the cyclic molecule can be measured by an analytical device such as GPC after isolating the cyclic molecule. In order to isolate the cyclic molecule, the terminal blocking groups of the polyrotaxane must be removed as a first step. For example, in the case of polyrotaxanes having terminal blocking groups bonded with amide groups or carbonyl groups, a method of heating under acid or base conditions and hydrolyzing the polyrotaxane can be used. The cyclic molecule can then be isolated by a conventional method such as reprecipitation, filtration, centrifugation, or membrane separation.
[0033] <chain molecule> The chain molecule of the polyrotaxane is not particularly limited as long as it can pierce the cyclic molecule in a skewered manner, is included in the cyclic molecule, and allows the cyclic molecule to rotate, slide, or move freely. In addition, the chain molecule is preferably a linear molecule. In the present disclosure, a linear molecule is considered to be a molecule having no branch in the main chain of the molecule. In addition, the length of the linear chain is not particularly limited.
[0034] The chain molecule is preferably at least one selected from the group consisting of polyalkylenes, polyesters, polyethers, polyamides, and polyacrylics, and among these, polyethers are more preferable. That is, the chain molecule is preferably a molecule having a polyether chain. More preferably, it is a molecule having a polyalkylene glycol chain, and even more preferably, it is a molecule having a polyethylene glycol chain.
[0035] <Blocking group> The chain molecule has two or more blocking groups at its terminals to prevent the cyclic molecules from being released. The blocking groups of the polyrotaxane can be used without any particular limitation as long as they have a structure that can prevent the cyclic molecules from being released. Examples of the blocking groups according to the present disclosure include bulky groups that physically prevent the cyclic molecules from being released, and ionic groups that electrically prevent the cyclic molecules from being released. Specific examples include dinitrophenyl groups, adamantyl groups, trityl groups, and pyrenyl groups. Specific examples include cyclodextrins and fluoresceins that are introduced as substituents at the terminals of the chain molecules. The blocking groups may also be derivatives or modified forms of the above.
[0036] <Bonded polyrotaxane> The cyclic molecules of the two or more polyrotaxanes may be bonded to each other by forming a chemical bond between them.
[0037] That is, the magnetic carrier contains a bound polyrotaxane formed by binding a first polyrotaxane and a second polyrotaxane, The first polyrotaxane and the second polyrotaxane may be bonded to each other by forming a chemical bond between a cyclic molecule contained in the first polyrotaxane and a cyclic molecule contained in the second polyrotaxane.
[0038] In the present disclosure, chemical bonds may be single bonds or bonds via various atoms or molecules (bonds via linkers).
[0039] Furthermore, a plurality of cyclic molecules contained in one polyrotaxane may be bonded to each other by forming a chemical bond.
[0040] <Magnetic carrier> The magnetic carrier according to the present disclosure contains a magnetic material-dispersed resin carrier core containing a magnetic material and a dispersion resin, and a coating resin that coats the surface of the magnetic material-dispersed resin carrier core. The magnetic material-dispersed resin carrier core is a carrier core in which a magnetic material is dispersed in a dispersion resin. In addition, the carrier core is preferably composed of a magnetic material and a dispersion resin.
[0041] <Magnetic material> Examples of the magnetic body according to the present disclosure include the following.
[0042] Magnetite particles, maghemite particles, or magnetic iron oxide particles containing at least one selected from silicon oxide, silicon hydroxide, aluminum oxide, and aluminum hydroxide; magnetoplumbite type ferrite particles containing barium, strontium, or barium-strontium; spinel type ferrite particles containing at least one selected from manganese, nickel, zinc, lithium, and magnesium, etc.
[0043] Of these, magnetic iron oxide particles are preferred.
[0044] The content of the magnetic material in the carrier core is preferably 80 to 98% by mass.
[0045] The magnetic material is preferably treated in whole or in part with a lipophilic treatment agent, which may be an organic compound having at least one functional group selected from the group consisting of an epoxy group, an amino group, a mercapto group, an organic acid group, an ester group, a ketone group, a halogenated alkyl group, and an aldehyde group, or a mixture thereof.
[0046] The lipophilic treatment agent is more preferably a coupling agent, more preferably at least one selected from the group consisting of a silane coupling agent, a titanium coupling agent and an aluminum coupling agent, and even more preferably a silane coupling agent.
[0047] In addition to the magnetic material, the following non-magnetic particles may be used in combination with the magnetic material.
[0048] Non-magnetic iron oxide particles such as hematite particles. Non-magnetic ferric oxide hydrate particles such as goethite particles. Non-magnetic inorganic compound particle powders such as titanium oxide particles, silica particles, talc particles, alumina particles, barium sulfate particles, barium carbonate particles, cadmium yellow particles, calcium carbonate particles, and zinc oxide particles.
[0049] When a mixture of magnetic material and non-magnetic particles is used, the mixing ratio of the magnetic material is preferably 30 mass %.
[0050] <Dispersion resin> The dispersion resin according to the present disclosure preferably includes at least one selected from the group consisting of phenolic resin, epoxy resin, and polyester resin. More preferably, it is a phenolic resin, such as a phenol-formaldehyde resin. Furthermore, it is preferable that these resins are the main component of the dispersion resin.
[0051] The content of the dispersion resin in the magnetic material-dispersed resin carrier core is preferably 2.0 to 20.0% by mass.
[0052] <Coating resin> The magnetic carrier also contains a coating resin that coats the surface of the carrier core. The content of the coating resin in the magnetic carrier is preferably 1.0 to 5.0% by mass.
[0053] The method for coating the surface of the magnetic carrier core with a resin is not particularly limited, but examples thereof include coating methods using a coating method such as a dipping method, a spraying method, a brush coating method, a dry method, and a fluidized bed method.
[0054] The resin used as the coating resin is preferably a vinyl resin which is a copolymer of a vinyl monomer having a cyclic hydrocarbon group in the molecular structure and another vinyl monomer. More preferred is a copolymer of a monomer including a (meth)acrylic acid ester having an alicyclic hydrocarbon group and a macromonomer. More preferred is a copolymer of a (meth)acrylic acid ester having an alicyclic hydrocarbon group, another (meth)acrylic monomer other than the (meth)acrylic acid ester having the alicyclic hydrocarbon group, and a macromonomer. In addition, the above alicyclic hydrocarbon group is preferably a cyclohexyl group.
[0055] Furthermore, conductive particles or particles or materials having charge control properties may be contained in the coating resin. Examples of conductive particles include carbon black, magnetite, graphite, zinc oxide, and tin oxide.
[0056] The amount of conductive particles added is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the coating resin in order to adjust the resistance of the magnetic carrier.
[0057] Examples of particles having charge controllability include particles of organic metal complexes, organic metal salts, chelate compounds, monoazo metal complexes, acetylacetone metal complexes, hydroxycarboxylic acid metal complexes, etc. Also included are particles of polycarboxylic acid metal complexes, polyol metal complexes, polymethyl methacrylate resins, polystyrene resins, melamine resins, phenolic resins, nylon resins, silica, titanium oxide, alumina, etc.
[0058] The amount of the particles having charge control properties added is preferably 0.5 parts by mass or more and 50.0 parts by mass or less with respect to 100 parts by mass of the coating resin in order to adjust the amount of triboelectric charge.
[0059] <Method of manufacturing magnetic carrier> The magnetic carrier according to the present disclosure can be manufactured, for example, by the method described in the examples below. Specifically, first, phenols and aldehydes are stirred in an aqueous medium in the presence of magnetic and non-magnetic inorganic compound particles, polyrotaxane, and a basic catalyst. Then, the phenols and aldehydes are reacted and cured to produce particles containing inorganic compound particles and phenol resin.
[0060] Alternatively, the magnetic carrier can be produced by a so-called kneading and grinding method in which a binder resin containing inorganic compound particles is ground. The former method is preferred in order to easily control the particle size of the magnetic carrier and to obtain a sharp particle size distribution.
[0061] <Toner> The toner according to the present disclosure is a toner having toner particles. The toner particles preferably have a weight average particle size (D4) of 3.0 to 10.0 μm.
[0062] <Binding resin> Examples of the binder resin used in the toner particles of the toner of the present disclosure include the following polymers. Homopolymers of styrene and its substituted derivatives, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; Styrenic copolymers such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, and styrene-acrylonitrile-indene copolymer; Polyvinyl chloride, phenolic resin, natural modified phenolic resin, natural resin modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester, polyurethane, polyamide, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin.
[0063] Among these, it is preferable to use polyester from the viewpoint of the chargeability of the toner.
[0064] <Wax> The toner particles may contain wax. Examples of the wax include the following. Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; Oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; Waxes whose main component is fatty acid esters, such as carnauba wax; Deoxidized carnauba wax and other fatty acid esters that have been partially or completely deoxidized.
[0065] Among these, from the viewpoint of low-temperature fixing property and hot offset resistance of the toner, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax are preferred.
[0066] In the present disclosure, from the viewpoint of electrostatic chargeability, hydrocarbon waxes are more preferred.
[0067] The content of the wax in the toner particles is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles. When the content of the wax is in the above range, it is more preferable from the viewpoint of charging property.
[0068] <Coloring agent> The toner particles may contain a colorant, such as a known yellow colorant, magenta colorant, cyan colorant, or black colorant.
[0069] Examples of black colorants include carbon black, and colorants toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0070] As the colorant, a pigment or a dye may be used alone, or a dye and a pigment may be used in combination.
[0071] The content of the colorant in the toner particles is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.
[0072] <Magnetic material> The toner of the present disclosure may be a magnetic toner. When used as a magnetic toner, it is preferable to use magnetic iron oxide as a magnetic material contained in the toner particles. Examples of magnetic iron oxide include magnetite, maghematite, and ferrite.
[0073] The content of the magnetic material in the toner particles is preferably 25 parts by mass or more and 95 parts by mass or less, and more preferably 30 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the binder resin in the toner particles.
[0074] <Charge control agent> The charge control agent includes a negative charge control agent and a positive charge control agent.
[0075] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.
[0076] When the toner particles contain a charge control agent, the charge control agent may be added internally or externally to the toner particles.
[0077] The content of the charge control agent in the toner particles is preferably 0.2 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.
[0078] <External additives> The toner of the present disclosure may contain an external additive in order to improve the fluidity of the toner or adjust the triboelectric charge amount. As the inorganic particulate external additive, inorganic particulates such as silicon oxide (silica), aluminum oxide (alumina), titanium oxide (titania), strontium titanate, and calcium carbonate are preferred. As the external additive other than inorganic particulates, for example, resin particulates such as vinyl resin, polyester, and silicone resin can be mentioned.
[0079] These inorganic fine particles and resin fine particles function as assistants for controlling the chargeability of the toner and for improving fluidity and cleaning.
[0080] <Toner manufacturing method> The toner of the present disclosure can be produced by a known method for producing toner particles, such as a melt kneading method, an emulsion aggregation method, or a solution suspension method.
[0081] The procedure for producing the toner by the pulverization method will be described below.
[0082] In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0083] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0084] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.
[0085] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).
[0086] Examples of methods for external addition include a method of stirring and mixing using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external addition device. In this case, external additives other than silica fine particles, such as a fluidizing agent, may be added as necessary.
[0087] <Various measurement methods> <Measurement of weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated.
[0088] The aqueous electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in deionized water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0089] Before performing measurements and analysis, the dedicated software is set up as follows.
[0090] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0091] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0092] The specific measurement methods are as follows (1) to (7).
[0093] (1) Pour about 200 ml of the above electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube.
[0094] (2) Place about 30 ml of the above electrolyte solution in a 100 ml flat-bottom glass beaker, and add about 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with deionized water as a dispersant.
[0095] (3) A specified amount of deionized water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the above-mentioned Conaminon N is added to this water tank.
[0096] (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized.
[0097] (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower.
[0098] (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner particles are dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000.
[0099] (7) Analyze the measurement data using the dedicated software attached to the device to calculate the weight average particle size (D4). When setting the graph / volume% with the dedicated software, the "average diameter" on the analysis / volume statistical value (arithmetic mean) screen is the weight average particle size (D4).
[0100] <Measurement of Weight Average Molecular Weight by GPC> The molecular weight distribution of the sample is measured by gel permeation chromatography (GPC) as follows.
[0101] First, dissolve the sample in tetrahydrofuran (THF) over 24 hours at room temperature. Then, filter the resulting solution through a solvent-resistant membrane filter "Maechory Disc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. Note that the sample solution is adjusted so that the concentration of the components soluble in THF is about 0.8% by mass. Using this sample solution, perform the measurement under the following conditions. · Equipment: HLC8120 GPC (Detector: RI) (manufactured by Tosoh Corporation) · Column: 7-series of Shodex KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) · Eluent: Tetrahydrofuran (THF) · Flow rate: 1.0 ml / min · Oven temperature: 40.0 °C · Sample injection volume: 0.10 ml When calculating the molecular weight of the sample, use the molecular weight calibration curve prepared using a standard polystyrene resin (for example, trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation).
[0102] <Measurement Method for Volume Average Particle Size (D50) of Magnetic Carrier and Magnetic Carrier Core> Particle size distribution and the like are measured using a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EX, manufactured by Nikkiso Co., Ltd.). The measurement is performed using a sample supplying device for dry measurement (product name: One-shot dry type sample conditioner Turbotrac, manufactured by Nikkiso Co., Ltd.). The supply conditions for Turbotrac are a dust collector as a vacuum source, an air volume of 33 l / sec, and a pressure of 17 kPa. Control is performed automatically on the software. The particle size is calculated as the 50% particle size (D50), which is the cumulative value of the volume average. Control and analysis are performed using the attached software (version 10.3.3-202D). The measurement conditions are as follows. ·Set Zero time: 10 seconds Measurement time: 10 seconds Number of measurements: 1 Particle refractive index: 1.81% ·Particle shape: non-spherical Measurement limit: 1408μm ·Measurement lower limit: 0.243μm ·Measurement environment: temperature 23℃ / humidity 50%RH EXAMPLES
[0103] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited thereto.
[0104] <Method of producing polyrotaxane A1> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and the mixture was stirred uniformly. 10.0g of the following polyrotaxane 1 (Polyrotaxane 1: SeRM Super Polymer SA1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has an acrylic skeleton, it has a vinyl polymerizable carbon-carbon double bond.) ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 150.0g of styrene, 50.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 3 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A1 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.
[0105] <Method of producing polyrotaxane A2> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred uniformly. 10.0g of the following polyrotaxane 2 (Polyrotaxane 2: SeRM Super Polymer SM1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has a methacryl skeleton, it has a vinyl polymerizable carbon-carbon double bond.) ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 250.0g of styrene, 75.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 5 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A2 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.
[0106] <Method of manufacturing polyrotaxane A3> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred uniformly. 10.0g of the above polyrotaxane 2 ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 300.0g of styrene, 100.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 8 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A3 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.
[0107] <Method of manufacturing polyrotaxane A4> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 600.0 g of xylene, 10.0 g of the above polyrotaxane 2, 150.0 g of styrene, 50.0 g of methyl methacrylate, and 1.5 g of initiator t-butyl peroxypivalate were added. After that, polymerization was carried out for 3 hours while rotating the stirrer and maintaining the temperature at 90°C, to obtain a reaction product. The obtained reaction product was washed and dried to obtain polyrotaxane A4, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.
[0108] <Polyrotaxane A5> Polyrotaxane A5 was prepared using the above-mentioned polyrotaxane 2.
[0109] <Method of manufacturing polyrotaxane A6> To a reaction vessel equipped with a stirrer, condenser, and thermometer were added the following materials: Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 350.0g Initiator: t-butyl peroxypivalate 1.5g After that, polymerization was carried out for 24 hours while rotating the stirrer and maintaining the temperature at 90°C, obtaining a reaction product. The reaction product was washed and dried to obtain polyrotaxane A6, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.
[0110] <Method of manufacturing polyrotaxane A7> To a reaction vessel equipped with a stirrer, condenser, and thermometer were added the following materials: Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 500.0g Initiator: t-butyl peroxypivalate 1.5g After that, polymerization was carried out for 24 hours while rotating the stirrer and maintaining the temperature at 90°C, obtaining a reaction product. The reaction product was washed and dried to obtain polyrotaxane A7, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.
[0111] <Method of manufacturing polyrotaxane A8> In 100 mL of pure water, add 2,2,6,6-tetramethyl-1-piperidinedioxy radical (TEMPO) (6.4 × 10 -4 mol) was added, and the pH was adjusted to 10-11. -4 mol), sodium hypochlorite (10 mL), and polyethylene glycol (n = 35,000, manufactured by Aldrich; hereafter referred to as PEG) were added to 7.0 × 10 -4 mol was added and stirred at room temperature for 10 to 15 minutes to oxidize the PEG terminal.
[0112] After adding 10 ml of ethanol, the pH was adjusted to 2, and dichloromethane extraction was performed using 100 ml of dichloromethane in three portions. The dichloromethane extract was evaporated to dryness under reduced pressure, dissolved in ethanol at 40-50°C, frozen for one day and night, and the PEG (PEG-COOH) with carboxylic acid terminal groups was collected by centrifugation. The obtained PEG-COOH was freeze-dried. The above synthesized PEG-COOH (8.6 × 10 -5 mol) and α-cyclodextrin (1.2 × 10 -2 mol) was dissolved in 100 mL of pure water and allowed to stand in a freezer overnight. The white paste-like product was then freeze-dried to obtain a powdered inclusion complex.
[0113] The following materials were dissolved in 100 mL of anhydrous DMF and reacted at 4° C. for 24 hours. ·14g of the above inclusion complex Adamantaneamine 1.1×10 -3 Mol Benzotriazol-1-yloxy-tris(dimethylamino)phosphonium salt 1.1×10 -3 Mol Ethylisopropylamine 1.2×10 -3 Mol Then, it was washed twice with a DMF / methanol solution (1:1, v / v) and methanol, and then washed with a mixed solution of 80 mL of anhydrous DMSO and 800 mL of pure water, and freeze-dried to obtain polyrotaxane A8 in which α-cyclodextrin was encapsulated.
[0114] <Preparation of treated magnetite> 4.0 parts of a silane coupling agent (3-(2-aminoethylamino)propyltrimethoxysilane) was added to 100 parts of magnetite powder having a number-average particle size of 0.30 μm, and the mixture was mixed and stirred at high speed in a container at a temperature of 100° C. or higher to obtain a treated magnetite.
[0115] <Toner 1 Manufacturing Example> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 100.0 mol% Terephthalic acid: 80.0 mol% based on the total number of moles of polycarboxylic acids Trimellitic anhydride: 20.0 mol% based on the total number of moles of polycarboxylic acids The monomer materials in the above ratio were charged into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Then, 1.5 parts by mass of tin 2-ethylhexanoate was added as a catalyst (esterification catalyst) to 100 parts by mass of the total amount of the monomer materials. Next, the inside of the reaction vessel was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the reaction was carried out for 2 hours while stirring at a temperature of 200°C.
[0116] Furthermore, the pressure in the reaction tank was reduced to 8.3 kPa and maintained for 1 hour, and then the pressure was cooled to 180 and the reaction was continued. After confirming that the softening point measured in accordance with ASTM D36-86 reached 122°C, the temperature was reduced to stop the reaction, and polyester resin 1 was obtained.
[0117] The resulting polyester resin 1 had a softening point (Tm) of 112°C and a glass transition temperature (Tg) of 63°C. Polyester resin 1: 100.0 parts by weight 3,5-di-t-butylsalicylic acid aluminum compound: 0.1 parts by mass Fischer-Tropsch wax (maximum endothermic peak temperature: 90°C): 5.0 parts by mass CI Pigment Blue 15:3 5.0 parts by weight The above raw materials were mixed in a Henschel mixer (product name: FM75J type, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s. -1 After mixing under conditions of 1000 rpm and a rotation time of 5 minutes, the mixture was kneaded in a twin-screw kneader (product name: PCM-30, manufactured by Ikegai Corporation) set at a temperature of 125°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed using a mechanical crusher (product name: T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles. The operating conditions of the rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) were a classification rotor rotation speed of 50.0 s -1 The weight average particle size (D4) of the obtained toner particles was 6.2 μm.
[0118] To 100.0 parts by mass of the obtained toner particles, 1.0 part by mass of hydrophobic silica fine particles having a primary average particle size of 15 nm and surface-treated with 20.0% by mass of hexamethyldisilazane were added and mixed in a Henschel mixer (product name: FM75J type, manufactured by Nippon Coke and Engineering Co., Ltd.) After that, the mixture was passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain toner 1.
[0119] <Preparation of coating resin solution 1> 28 parts by weight of methyl methacrylate macromer (average value n=50) having an ethylenically unsaturated group at one end and a weight average molecular weight of 5,000 Cyclohexyl methacrylate 70 parts by weight Methyl methacrylate 2 parts by weight The above materials were added to a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a grinding stirrer. 90 parts by mass of toluene, 110 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were further added. The resulting mixture was kept at a temperature of 70°C under a nitrogen stream for 10 hours to obtain a resin solution (resin solid content 33% by mass).
[0120] The following materials were added to the obtained resin solution (an amount such that the resin solid content was 10 parts), and then thoroughly mixed with a homogenizer to obtain a coating resin solution 1. Crosslinked melamine particles (maximum peak particle size based on number distribution is 0.2 μm) 0.5 parts by weight Carbon black fine particles (maximum peak particle size based on number distribution is 0.04μm, specific resistance is 9.0×10 -1 Ω cm) 0.5 parts by mass Toluene 70 parts by weight
[0121] <Example 1> <Magnetic Carrier 1 Manufacturing Example> Phenol 6.0 parts by weight 9.0 parts by weight of the following formaldehyde solution (Solution 1) (Solution 1: 40% formaldehyde, 10% methanol, 50% water) 84.52 parts by weight of the above treated magnetite 0.48 parts by mass of the above polyrotaxane A1 The above materials, 5 parts by mass of 28% ammonia water, and 20 parts by mass of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and maintained at 85°C while stirring and mixing, and a polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to a temperature of 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain magnetic carrier core particles, which are resin particles in which a magnetic substance is dispersed.
[0122] Next, the following materials were charged into a planetary mixer (Nauta Mixer VN type, manufactured by Hosokawa Micron Corporation) maintained at a reduced pressure (1.5 kPa) and a temperature of 60°C. Obtained magnetic carrier core particles 100.0 parts by mass Coating resin solution 1 (amount that results in a coating resin content of 2.0 parts by mass per 100 parts by mass of magnetic carrier core particles) The method of addition was as follows: first, 1 / 2 the amount of resin solution was added to the magnetic carrier core particles, and the solvent was removed and the coating operation was performed for 30 minutes, and then another 1 / 2 the amount of resin solution was added, and the solvent was removed and the coating operation was performed for 30 minutes.
[0123] The magnetic carrier coated with the coating resin composition was then transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated for 2 hours at 120°C in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified with a wind classifier to obtain magnetic carrier 1. The volume average particle size of the magnetic carrier obtained was 35.2 μm.
[0124] <Example of manufacturing two-component developer> The above toner 1 and magnetic carrier 1 were mixed for 0.5 seconds using a V-type mixer (product name: V-10 type, Tokuju Manufacturing Co., Ltd.) so that the toner concentration became 9% by mass. -1 and 5 minutes to obtain a two-component developer.
[0125] <Example of manufacturing replenishment developer> The above toner 1 and magnetic carrier 1 were mixed for 0.5 seconds using a V-type mixer (product name: V-10 type, Tokuju Manufacturing Co., Ltd.) so that the toner concentration became 90% by mass. -1 The mixture was mixed for 5 minutes to obtain a replenishment developer.
[0126] <Evaluation> The following evaluations were carried out using the magnetic carrier 1, the obtained two-component developer, and the obtained replenishment developer.
[0127] <Measurement of carrier strength> First, the volume average particle diameter of the magnetic carrier 1 was measured by the above measurement method, and the value was taken as D0 (μm). Next, 100 g of the magnetic carrier 1 was put into a sample mill (Kyoritsu Riko Co., Ltd., SK-M10), and the rotation speed was set to 16500 rpm, and the grinding process was performed for 60 seconds. After that, the volume average particle diameter of the carrier after the grinding process was measured by the above measurement method, and the value was taken as D1 (μm). Then, the above D0 and D1 were substituted into the following formula to calculate the particle diameter change rate of the carrier. The results are shown in Table 2. If the particles crack, chip, or fine particles are generated due to stress caused by the grinding process, the volume average particle diameter after the grinding process will be smaller, so the change rate of the volume average particle diameter before and after the grinding process was used as an index of the carrier strength. Carrier strength (particle size change rate) (%) = [(D0-D1) / D0] × 100 D0: Volume average particle size of carrier before crushing (μm) D1: Volume average particle size of the carrier after crushing (μm) (The volume average particle size was measured by the above-mentioned measurement method.)
[0128] <Fog evaluation> A modified full-color copier (product name: imageRUNNER ADVANCE C5560) manufactured by Canon Inc. was used as the image forming apparatus. The modification was to make it possible to change the process speed and the developing bias. The process speed of the modified machine was adjusted so that it could output at 380 mm / sec in normal durability mode and 460 mm / sec in stress durability mode, and the developing bias was adjusted so that the initial image density was 1.55. The paper used for evaluation was A4-size plain paper for copying (product name: GF-C081, basis weight: 81.4 g / m 2 (sold by Canon Marketing Japan Inc.) was used.
[0129] In addition, when forming an image, the developer in the cyan developing device was replaced with the above-mentioned two-component developer, and the developer in the cyan refill developer container was replaced with the above-mentioned refill developer. The reason why the two-component developer and the refill developer are used in this evaluation is because using both of them is a normal mode when using the above-mentioned image forming apparatus.
[0130] First, a durability test of 300,000 sheets was conducted under a high temperature and high humidity environment (30°C / 80%RH) at a process speed of 380mm / sec with a FFH output chart with an image ratio of 40%. After that, it was left to stand in the same environment for 3 days, and a blank image (00h image) was output after the standing. The average reflectance (%) of the blank image before the output and the blank image after the output was measured, and the difference (%) between the average reflectances was taken as the fog density to evaluate the image fog. The results are shown in Table 2. The average reflectance was measured using a "REFLECTMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.).
[0131] The process speed was changed to 460 mm / sec, and the same operation as above was carried out to calculate the image fog density. The results are shown in Table 2.
[0132] <Toner scattering> After the durability tests at each process speed, the developing unit was removed from the machine and set on an idle rotating jig that rotates the developer carrier. Then, an A4 sheet of paper was placed directly below the developer carrier and rotated for 10 minutes at the same peripheral speed as the process speed at which the image was output. The mass of the toner that fell onto the paper was measured to evaluate toner scattering. The results are shown in Table 2.
[0133] <Examples 2 to 13> Magnetic carriers 2 to 13 were obtained in the same manner as in Example 1, except that the types and amounts of materials used were changed as shown in Table 1. Two-component developers and replenishment developers were then prepared and evaluated in the same manner. The evaluation results are shown in Table 2.
[0134] <Example 14> A two-component developer and a replenishment developer were prepared and evaluated in the same manner as in Example 1, except that the magnetic carrier 1 was changed to the following magnetic carrier 14 and the types and parts of the materials used were changed as shown in Table 1. The evaluation results are shown in Table 2.
[0135] [Manufacturing example of magnetic carrier 14] Polyester resin ("Tufton" TTR-2: Kao Corporation, glass transition point 65°C, acid value 3mgKOH / g) 10.0 parts by mass 64.05 parts by weight of the above treated magnetite Polyrotaxane A8 6.5 parts by weight The above materials were mixed and stirred in a stirrer ("Super Mixer" SMV-20: manufactured by Kawata Corporation), and then melt-kneaded in a twin-screw kneading extruder (PCM-30: manufactured by Ikegai Iron Works). After cooling, the kneaded material was coarsely pulverized to 2 mm diameter paths in a coarse pulverizer (UG-210KGS: manufactured by Horai Iron Works), and then medium pulverized in a medium pulverizer ("Fine Mill" FM-300N: manufactured by Nippon Pneumatic Industrial Co., Ltd.). After that, it was passed through a fine powder classifier ("Separator" DS-5UR: manufactured by Nippon Pneumatic Industrial Co., Ltd.) to obtain magnetic carrier core particles 14.
[0136] <Comparative Example 1> A magnetic carrier 15 was obtained in the same manner as in Example 1, except that the types and amounts of materials used were changed as shown in Table 1. Then, a two-component developer and a replenishment developer were prepared in the same manner as in Example 1, and evaluated. The evaluation results are shown in Table 2.
[0137] [Table 1]
[0138] In Table 1, the epoxy resin was EPICLON HP-6000 (product name, manufactured by DIC Corporation). The molecular weight of the cyclic molecule was measured by the method described above.
[0139] [Table 2]
Claims
1. A magnetic carrier comprising a magnetic material-dispersed resin carrier core containing a magnetic material and a dispersion resin, and a coating resin that coats the surface of the magnetic material-dispersed resin carrier core, The magnetic material-dispersed resin carrier core contains polyrotaxane, The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; A magnetic carrier comprising:
2. 2. The magnetic carrier according to claim 1, wherein the cyclic molecule is a molecule having a cyclodextrin skeleton.
3. 3. The magnetic carrier according to claim 2, wherein the molecule having a cyclodextrin skeleton has a weight average molecular weight of 1,000 to 50,000.
4. 4. The magnetic carrier according to claim 2, wherein the molecule having a cyclodextrin skeleton comprises a cyclodextrin and a side chain bonded to the cyclodextrin.
5. 5. The magnetic carrier according to claim 4, wherein the side chain has a polyester structure or a vinyl polymer structure.
6. 6. The magnetic carrier according to claim 1, wherein a content ratio of the polyrotaxane is 0.2% by mass or more and 30.0% by mass or less with respect to the mass of the dispersion resin.
7. 7. The magnetic carrier according to claim 1, wherein the dispersion resin comprises at least one selected from the group consisting of a phenol resin, an epoxy resin, and a polyester resin.
8. 8. The magnetic carrier according to claim 1, wherein the content of the dispersion resin in the magnetic material-dispersed resin carrier core is 2.0 to 20.0% by mass.
9. the polyrotaxane comprises a first polyrotaxane and a second polyrotaxane, the magnetic carrier contains a bound polyrotaxane formed by binding the first polyrotaxane and the second polyrotaxane, The first polyrotaxane and the second polyrotaxane are bonded to each other by forming a chemical bond between a cyclic molecule of the first polyrotaxane and a cyclic molecule of the second polyrotaxane. The magnetic carrier according to any one of claims 1 to 8.
10. 10. The magnetic carrier according to claim 1, wherein the chain molecule is a molecule having a polyalkylene glycol chain.
11. A two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 10. A two-component developer comprising:
12. A replenishment developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 10. A replenishing developer comprising:
Citation Information
Patent Citations
Magnetic material distribution type resin carrier and two-component developer
JP2003295523A
Light-controlling panel
JP2012189746A
Electrophotographic member
JP2014066857A
Electrophotographic member, process cartridge and electrophotographic device
JP2017010013A
Temperature responsive polyrotaxane gel and drug carrier
JP2017031258A